THE USE OF ARTIFICIAL INTELLIGENCE-BASED CHATBOTS IN THE EDUCATIONAL SYSTEM (Scientific journal of the Fergana State University, 2023)
The integration of artificial intelligence (AI) technologies into education has shown promising opportunities for revolutionizing the learning process. ChatGPT, a conversational artificial intelligence model developed by Open AI, has attracted considerable attention as a potential tool for educational purposes. This article is aimed at exploring the potential of using AI as a learning tool in educational institutions. Thanks to a literature review and analysis of relevant articles, including "How to use ChatGPT as a Learning Tool" by Ashley Abramson (2023) and "ChatGPT: Educational Friend or Foe?" Katie Hirsch-Pasek and Elias Blinkoff (2023), this study examines various aspects of the usefulness, benefits and limitations of ChatGPT in facilitating learning. The data obtained emphasize the importance of teachers' understanding of ChatGPT's capabilities and the need for effective integration strategies to maximize its educational potential.